PROTOTIPE INSTALASI PENGOLAHAN AIR LIMBAH INDUSTRI PENGOLAHAN IKAN DI KECAMATAN MUNCAR, KABUPATEN BANYUWANGI - ., Setiyono; Yudo, Satmoko (Jurnal Teknologi Lingkungan, 2010)
Muncar region known as the area of the fish and the fish processing industry. Many of the fish processing industries in large scale, small scale and household at this time growing so rapidly. With the rapid growth of the fish processing industry in the Muncar city has provided a very significant impact on the city growth, which eventually brought the various impacts, whether they are positive or negative. One of the negative impact of processing industry growth in Muncar is environmental of pollution is the discharge of liquid waste from industrial fish-processing industry. Low level of understanding IPAL waste management system and cause difficulties to manage the waste, therefore almostall waste that generated in the region immediately removed to the public channels. Waste disposal without treatment is causing high level of environmental pollution in the vicinity of the location of industry. One effort to solve the problem of waste-processing technology is determine processingof waste water and fish processing, it has been done to test prototype installation processing waste water in one of the fish processing industry in the Muncar District. Key words : fish processing industry waste water, environmetal pollution, waste water processing prototype.